A Note on the Efficiency Effects of Agglomeration Economies: Turkish Evidence - Timurçin, Deniz; Omay, Tolga; Arin, K. Peren (Journal of Reviews on Global Economics, 2014)
By using a very novel dataset from Turkish SMEs, this paper investigates the effects of agglomeration economies on productive and allocative efficiency. After controlling for unobserved heterogeneity at the time level, our empirical results from ordered panel probit models provide evidence that clusters have no statistically significant effect on productive efficiency but a negative effect on allocative efficiency. We also show that the increase in prices is not due to increased product differentiation; therefore, it is most likely due to collusion.